Assessing Asiatic cheetah’s individual diet using metabarcoding and its implication for conservation - Leili Khalatbari; Bastian Egeter; Hamed Abolghasemi; Ehsan Hakimi; Taher Ghadirian; Amir Hosein Khaleghi Hamidi; Houman Jowkar; Urs Breitenmoser; José Carlos Brito (Scientific Reports, 2022)
Abstract Knowledge on diet composition allows defining well-targeted conservation measures of large carnivores. Little is known about ecology of critically endangered Asiatic cheetah, especially the overall diet and its possible regional differences. We used cheetah scats, metabarcoding technique and microsatellite markers to assess the individual and overall diet composition of the species across its entire range in Asia. Cheetahs were primarily predating on mouflon; following by ibex, cape hare and goitered gazelle. Despite their high availability, small-sized livestock was never detected. Goitered gazelles were only detected in an area where the habitat is mainly flatlands. In hilly areas, mouflon was the most frequent prey item taken. Ibex was typically taken in rugged terrain, but mouflon was still the most frequently consumed item in these habitats. High consumption of mouflon in comparison to goitered gazelle suggests that human pressure on lowland habitats has possibly forced Asiatic cheetahs to occupy suboptimal habitats where gazelles are less abundant. The protection of flatlands and the removal of livestock from them are needed to ensure the long-term survival of Asiatic cheetah. The laboratory and bioinformatics pipelines used in this study are replicable and can be used to address similar questions in other threatened carnivores.